New Medieval literatures 21 - Scase, Wendy 1955-; Ashe, Laura ca. 20./21. Jh; Knox, Philip 1988-; Robertson, Kellie 1968- (D.S. Brewer, 2021)
Cutting-edge and fresh new outlooks on medieval literature, emphasising the vibrancy of the field
Title from publisher's bibliographic system (viewed on 27 Apr 2021)
Keywords: Literature, Medieval / History and criticism